The impact of COVID-19 Pandemic on business / Norhidayah Ali ... [et al.] - Ali, Norhidayah; Andin Salamat, Azni Syafena; Mohamed Isa, Zuraidah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
COVID-19 has been declared as a deadly, infectious disease globally. It has triggered chaos in many parts of the world, impacting individuals, businesses, and governing bodies in almost every country. COVID-19 has posed immense challenges on most businesses worldwide, including in Malaysia. Nonetheless, some businesses have risen to turn threats into opportunities such as by carrying out online businesses and delivery services while adhering to the standard operating procedures (SOP) endorsed by the government. In Malaysia, all businesses were forced to close down temporarily during the early phases of the Movement Control Order (MCO) period except for those involved in essential services such as banking, basic utilities supply, and food and beverage supply. Employers were encouraged to pay full salary to employees, regardless of whether they were working from the office or from home. However, when business stability is threatened, employers tend to reduce employees' salary or working hours to prevent dismissal (Donovan & Ho, 2020).